Strategic Human Capital and Academic Performance: The Mediating Role of Work Engagement in Higher Education - Yuyuk Liana; Rina Irawati; Imama Zuchroh (AIBPM Publisher, 2026)
Higher education institutions are increasingly relying on the human capital of their faculty to maintain the academic quality of research articles and institutional competitiveness. This study examines the role of strategic human capital which includes individual and psychological capital (PsyCap) in enhancing faculty performance effectiveness, with work engagement serving as a mediating variable. Using a quantitative research design, data were collected from 120 tenured faculty members at private universities in East Java under the jurisdiction of LLDIKTI Region VII, via a structured questionnaire. Data analysis was conducted using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results indicate that individual development has a significant effect on faculty performance (effect size = 0.307; p 0.001) and work engagement (effect size = 0.672; p 0.001). PsyCap also demonstrated a significant influence on performance (r² = 0.243; p = 0.001) and work engagement (r² = 0.198; p = 0.007). Furthermore, work engagement was found to be a significant predictor of faculty performance (? = 0.437; p 0.001) and acted as a mediator between strategic human capital components and performance outcomes. These findings extend the Job Demands-Resources (JD-R) framework within the context of higher education, emphasizing the strategic value of psychological and developmental resources in fostering work engagement and academic performance.